THE PLACE OF ACCOUNTING IN THE COMMERCE CURRICULUM. - Madden, J. T.; Stevenson, R. A.; Gray, W. R. (The Accounting Review, 1928)
Abstract Courses in accounting occupy a distinctive place in the curriculum of every collegiate school of business. The particular location in the course of study, however, differs quite widely between the various institutions. Furthermore, the character of the subject matter taught under the title of accounting means different things in the several schools. In view of the fact that professional schools of business are still in the early developmental stage, one can hardly hope for anything approaching standardization in curriculum making. Annual revision of courses will continue until the various professional business occupations become more clearly defined than they are at present. One of the chief difficulties encountered in attempting to generalize on this subject is the number of different types of institutions offering collegiate instruction in business. There are the four-year schools which admit students directly from high school, the two-year courses to which students are admitted who have completed either two or three years in an arts college, and the graduate schools which offer instruction only to those who have completed a full four-year academic course. In addition to these, there are the schools, which have specialized in certain fields such as retailing, and personnel administration. Each of these institutions is attempting to adapt its course requirements to meet the demand for technically trained men in business.